CHARLIE’S ANXIETY ASSOCIATED WITH HER DEFENSE MECHANISM IN JONATHAN STROUD’S THE LEAP NOVEL - Ali, Saheriah; Kuncara, Singgih Daru; Rahayu, Famala Eka sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2023)
ABSTRACTThis study is aimed to find out the anxiety and defense mechanisms experienced by the main character. As it is known, anxiety is a psychological problem of someone when a person feels threatened and overwhelmed as their world is about to collapse. As well as human in real life, anxiety and defense mechanism can also be represented by the characters in literary works. Based on that, the writer decided to analyze The Leap novel written by Jonathan Stroud and used it as the object of this study. A descriptive qualitative method was employed to fulfil the objectives of this research. As the data, this study employed words, phrases, clauses, sentences that were taken from The Leap in the novel. The results showed Charlie’s character experienced anxieties which are neurotic anxiety and moral anxiety. The conclusion of this study considered Charlie’s character experienced neurotic anxiety was indicated by panics and hallucinations. Charlie’s anxiety starts to arise when she had a flashback about what happened to her and her friend, Max. Meanwhile Charlie’s feelings of fear are caused by the people around her who always blamed her for not being able to save Max from drowning in the lake. Charlie’s moral anxiety was indicated by a constant guilt and even gasping for breath. This anxiety reflected because she felt guilty for what happened to Max as she got a dream that she could save Max if she could pursue Max in her dreams. Additionally, Charlie also employed defense mechanisms which are displacement and denial. Displacement is done when Charlie used other means as a result of her fear of something so that she could bear with it. Meanwhile denial was done when Charlie could not accept the fact that Max was dead.Key words: anxiety, defense mechanism, The Leap novel